Augmented Reality Guided Needle Biopsy of Soft Tissue: A Pilot Study - Asgar-Deen, David; Carriere, Jay; Wiebe, Ericka; Peiris, Lashan; Duha, Aalo; Tavakoli, Mahdi (Frontiers in Robotics and AI, 2020)
Percutaneous biopsies are popular for extracting suspicious tissue formations (primarily for cancer diagnosis purposes) due to the: relatively low cost, minimal invasiveness, quick procedure times, and low risk for the patient. Despite the advantages provided by percutaneous biopsies, poor needle and tumor visualization is a problem that can result in the clinicians classifying the tumor as benign when it was malignant (false negative). The system developed by the authors aims to address the concern of poor needle and tumor visualization through two virtualization setups. This system is developed to track and visualize the needle and tumor in three-dimensional space using an electromagnetic tracking system. User trials were conducted in which the 10 participants performed a total of 6 trials each guiding the biopsy needle to the desired location. The users guided the biopsy needle to a desired point on an artificial spherical tumor (diameters of 30 mm, 20 mm, and 10 mm) using the 3D augmented reality (AR) overlay for 3 trials, and a projection on a second monitor (TV) for the other 3 trials. From the randomized trials, it was found that the participants were able to guide the needle tip 6.5 - 3.3 mm away from the desired position with a angle deviation of 1.96 - 1.10° in the AR trials, compared to values of 4.5 - 2.3 mm and 2.70 - 1.67° in the TV trials. The results indicate that for simple stationary surgical procedures an AR display is non-inferior a TV display.